2020
DOI: 10.1159/000507774
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Awareness and Longitudinal Health Outcomes: Results from the REasons for Geographic And Racial Differences in Stroke Study

Abstract: Background: The majority of people with chronic kidney disease (CKD) are unaware of their kidney disease. Assessing the clinical significance of increasing CKD awareness has critical public health and healthcare delivery implications. Whether CKD awareness among persons with CKD is associated with longitudinal health behaviors, disease management, and health outcomes is unknown. Methods: We analyzed data from participants with CKD in the REasons for Geographic And Racial Differences in Stroke study, a nation-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Last, in our analysis, few patients aged <50 years were included as the BIS cohort recruited only persons aged 70 years and older. However, in DIACORE and CAD-Ref, the proportion of younger patients was 25% and comparable to other cohorts [43]. Proportions of unaware CKD patients in age group <50 years were 82% (DIACORE) and 92% (CAD-Ref).…”
Section: Strengths and Limitationssupporting
confidence: 66%
See 1 more Smart Citation
“…Last, in our analysis, few patients aged <50 years were included as the BIS cohort recruited only persons aged 70 years and older. However, in DIACORE and CAD-Ref, the proportion of younger patients was 25% and comparable to other cohorts [43]. Proportions of unaware CKD patients in age group <50 years were 82% (DIACORE) and 92% (CAD-Ref).…”
Section: Strengths and Limitationssupporting
confidence: 66%
“…However, CKD prevalence in patients with eGFR < 60 mL/min/1.73 m 2 (CKD Stages 3-4) might be overestimated. As many cross-sectional epidemiologic studies are limited to a single eGFR measurement in defining CKD, the comparability of our results is facilitated [37,43,44]. However, we do not have information on educational attainment or social status, which might be associated with patient awareness.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Similarly, Chu et al 4 found that between 2011 and 2016, CKD awareness ranged from 10% to just 49% among low- and high-risk groups, respectively. Tummalapalli et al 5 found that of 6,529 participants with CKD, just 4.4% were aware of their CKD. CKD awareness was associated with 1.44 increased odds of ESKD.…”
Section: What Information Should Be Communicated Earlier In the Diseamentioning
confidence: 99%
“…These studies and others suggest that CKD awareness, although universally low, is higher among people with more advanced disease, highlighting the need for education at early stages of CKD. 5 …”
Section: What Information Should Be Communicated Earlier In the Diseamentioning
confidence: 99%
See 1 more Smart Citation